PENGARUH PEMBERIAN BOOKLET PINTAR ASI TERHADAP PENGETAHUAN DAN SIKAP IBU NIFAS DI PMB PERA - Sitepu, Stefani Anastasia; Hutabarat, Vitrilina (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Background: Breast Milk is the best source of nutrition for infants, especially during the first six months of life. However, many postpartum mothers still lack adequate knowledge and a positive attitude towards exclusive breastfeeding. This study aimed to determine the effect of a smart breastfeeding booklet on the knowledge and attitudes of postpartum mothers. This was a quantitative study with a one-group pretest-posttest design. The sample consisted of 25 postpartum mothers selected using total sampling. Instruments used were knowledge and attitude questionnaires. Data were analyzed using paired t-test. Result showed an increase in knowledge from 6.20 to 10.16 and attitude from 29.84 to 44.80 after the intervention. Statistical test indicated a significant effect (p=0.000). It can be concluded that the smart breastfeeding booklet is effective in improving maternal knowledge and attitudes.